Herbaspirillum psychrotolerans sp. nov., a member of the family Oxalobacteraceae from a glacier forefield. - Bajerski, Felizitas; Ganzert, Lars; Mangelsdorf, Kai; Lipski, André; Busse, Hans-Jürgen; Padur, Lisa; Wagner, Dirk (International Journal of Systematic and Evolutionary Microbiology, 2013)
A novel psychrotolerant, Gram-negative, shiny white, curved-rod-shaped, facultatively anaerobic bacterium PB1T was isolated from a soil sample collected from a glacier forefield of the Larsemann Hills, East Antarctica. Isolate PB1T has catalase and low urease activity and hydrolyses gelatin and starch. Strain PB1T is able to grow between −5 °C and 30 °C with optimum growth at 14–20 °C. Glycerol, dl-arabinose, d-xylose, d-galactose, d-fructose, d-lyxose, d-fucose and potassium gluconate are used as sole carbon sources. The major quinone is ubiquinone Q-8. The major fatty acids (>10 %) for PB1T are C16 : 0 (19.1 %), C16 : 1ω7cis (44.6 %) and C18 : 1ω7cis (16.2 %). The major polyamines are putrescine [54.9 µmol (g dry weight)−1] and 2-hydroxy putrescine [18.5 µmol (g dry weight)−1]. DNA G+C content is 62.5 mol%. Strain PB1T is phylogenetically related to species of the genus Herbaspirillum, with highest 16S rRNA gene sequence similarities to Herbaspirillum canariense (97.3 %), Herbaspirillum aurantiacum (97.2 %), Herbaspirillum soli (97.2 %) and Herbaspirillum frisingense (97.0 %). The DNA–DNA relatedness values were below 30 % between PB1T and the type strains of Herbaspirillum canariense, Herbaspirillum aurantiacum and Herbaspirillum soli. The different geographical origin of strain PB1T from its closest phylogenetic relatives resulted in different phenotypic and genotypic specifications, whereby strain PBT represents a novel species of the genus Herbaspirillum, for which the name Herbaspirillum psychrotolerans is proposed. The type strain is PB1T (DSM 26001T = LMG 27282T).